The limits of transnational law : refugee law, policy harmonization and judicial dialogue in the European Union / edited by Guy S. Goodwin-Gill and Hélène Lambert. - Lambert, Hélène; Goodwin-Gill, Guy S. (Cambridge University Press, 2010)
State authority and power have become diffused in an increasingly globalized world characterized by the freer trans-border movement of people, objects and ideas. As a result, some international law scholars believe that a new world order is emerging based on a complex web of transnational networks. Such a transnational legal order requires sufficient dialogue between national courts. This 2010 book explores the prospects for such an order in the context of refugee law in Europe, focusing on the use of foreign law in refugee cases. Judicial practice is critically analysed in nine EU member states, with case studies revealing a mix of rational and cultural factors that lead judges to rarely use each others' decisions within the EU. Conclusions are drawn for the prospects of a Common European Asylum System and for international refugee law.